Exploring Six Muslim Teachers’ Coping Strategies in Overcoming Mental Illness - Abd Karim, Aishah Hanim (IIUM Journal of Educational Studies, 2019)
The main purpose of this qualitative research was to explore Muslim Malaysian teachers’ perspective of both mental illness and well-being. The study aimed to understand the teachers’ coping strategies in overcoming mental illness and the relationship between spiritual practices and mental well-being. Six Muslim Malaysian teachers were involved in this study. All of them were teachers at the government public schools and they had experienced mental illnesses during their career. The six teachers were interviewed using semi-structure interview protocol. The interviews took place at different times and settings. Content and inductive analysis was used to interpret data for all participants. Findings of this study showed four themes, namely medical treatment, religion, family and societal support, and positivity were dominant. The four subthemes emerged from the religion theme were prayers, reading the Qur’an, protective factor, and diseases of the heart. These subthemes showed the relationship between spiritual practices and mental well-being. Finally, the study revealed the importance of seeking professional help, getting appropriate medical treatment, and engaging in various spiritual practices such as performing the five daily prayers, zikr, salawat shifa,’ and reading the Qu’ran in bringing the feeling of peace and calmness in these Muslim teachers’ lives, hence helping them to cope and become productive teachers.